Eugenol Improves Insulin Secretion and Content of Pancreatic Islets from Male Mouse - Ali Akbar Oroojan (International Journal of Endocrinology)
Glucose homeostasis is required for control of insulin secretion. Phenolic compounds improved glucose-stimulated insulin secretion (GSIS). Eugenol is a phenolic compound that may increase GSIS. So, it was decided to investigate the effect of eugenol on the insulin secretion and content of pancreatic islets from the male mice. In this experimental study, 3-month-old NMRI mice (20–25 g) were prepared. The pancreatic islets of Langerhans were isolated using the collagenase digestion method and divided into 12 groups: glucose 2.8, 5.6, and 16.7 mM, glucose 2.8 mM + eugenol 50, 100, and 200 µM, glucose 5.6 mM + eugenol 50, 100, and 200 µM, and glucose 16.7 mM + eugenol 50, 100, and 200 µM. The islet’s insulin secretion and content were measured after 1 hour and 24 hours incubation at 37°C, respectively, by the ELISA assays method and related commercial kit. Present results showed that all doses of eugenol increased islet’s insulin secretion and content in the medium containing glucose concentrations 2.8, 5.6, and 16.7 mM (P < 0.05). In conclusion, eugenol as a phenolic compound increased insulin secretion and content of pancreatic islets. The moderate dose of this compound enhanced insulin secretion during hypo- and hyperglycemic conditions, as well as a high dose of eugenol, increased insulin content. Finally, present research suggested that the administration of eugenol 100 µM was suitable for the early stage of T2DM as well as eugenol 200 µM for the advanced stage of this disease.